Knowledge, Attitude and Perceived barrier towards Medical Research among Undergraduates and Postgraduates Medical Students of Nepalgunj Medical College - Shrestha, Merina; K.C., Rupak; Luintel, Prabesh; Joshi, Anjali; Mahat, Rajendra (Journal of Nepalgunj Medical College, 2022)
Introduction: Medical science is one of the most advance and modern technology over the course of time period with extensive research and scientific knowledge of human body and health care to make incredible changes enabling the population remain healthy with mere absence of disease or infirmity. Research is considered as one of the useful measures to track the scientific advancement of a country. Promoting research skills in undergraduate and post graduate medical students help to develop scientific advancement in medical field of a country.Aims: To assess knowledge, attitude, and perceived barriers among undergraduate and postgraduate medical students.Methods: An institutional based cross sectional analytical study covering total 224 undergraduate and postgraduate medical students of Nepalgunj Medical College was from January 2022 to April 2022. A pre tested, pre designed, sets of questionnaire were provided to all recruited participants after obtaining informed written consent. Then informations generated by the study were analyzed for scientific result by using descriptive analysis and independent T- test.Results: Male students were 135(60.3%) whereas female students were 89(39.7%) only. The mean knowledge score was 33.69 ± 3.8 and mean attitude score was 19.67 ± 2.34. The average 100(44.6%) had good knowledge and 118(52.7%) had positive attitude towards medical research. Most common perceived barrier was not having proper mentoring and research familiarity. Seventy Six(39.6%) undergraduate students had behavioral hesitation to participate in research while 21(65.6%) post graduate students showed social factor as one of the hesitancy to involve in research.Conclusion: Most of the participants had good knowledge regarding research and expressed positive attitude toward involvement in research activity. Some of barriers were lack of funds, awareness and research skills. This study would improve scientific knowledge and research skills for academicians and clinicians too.